Proceedings. 13th International Conference on Computer Communications and Networks (IEEE Cat. No.04EX969)
DOI: 10.1109/icccn.2004.1401632
|View full text |Cite
|
Sign up to set email alerts
|

A location-based routing algorithm for vehicle to vehicle communication

Abstract: In this paper, we present a location-based routing algorithm with cluster-based flooding for vehicle to vehicle communication. We consider a motorway environment with associated high mobility and contrast and compare positionbased and non-position-based routing strategies, along with a limiting function for flood mechanisms in reactive ad-hoc protocols. The performance of Dynamic Source Routing (DSR) and Ad-Hoc On-demand Distance Vector Routing (AODV) for non-positional and Location Routing Algorithm with Clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Improving the neighbor detection algorithm in AODV, based on the differentiation between good and bad neighbors, using signal-to-noise ratio (SNR) value was proposed and experimentally verified in the work of Krco and Dupcinov [15]. Other approaches that employ location based and cluster-based location routing algorithms for inter-vehicle and vehicle-to-vehicle communications were reported in the work of Santos et al [16,17], respectively, and their performances were compared to AODV and DSR protocols. It was reported that enabling Hello messages decreased AODV performance, compared to the other two protocols.…”
Section: Related Workmentioning
confidence: 99%
“…Improving the neighbor detection algorithm in AODV, based on the differentiation between good and bad neighbors, using signal-to-noise ratio (SNR) value was proposed and experimentally verified in the work of Krco and Dupcinov [15]. Other approaches that employ location based and cluster-based location routing algorithms for inter-vehicle and vehicle-to-vehicle communications were reported in the work of Santos et al [16,17], respectively, and their performances were compared to AODV and DSR protocols. It was reported that enabling Hello messages decreased AODV performance, compared to the other two protocols.…”
Section: Related Workmentioning
confidence: 99%
“…The main contribution of our work is the rebroadcast and gateway selection mechanism we have developed. We have implemented a re-broadcast strategy, where only gateways that belong to different cluster-heads re-broadcast the location request packets, thus improving the routing overhead in dense networks (Santos et al, 2004).…”
Section: Reactive Location-based Routing Algorithm With Cluster-basedmentioning
confidence: 99%
“…We have implemented the same short-term predictive algorithm used in LORA-CBF (Santos et al, 2004) and the same physical and MAC layer in GPSR.…”
Section: A Comparison Of the Lora-cbf And Gpsr Algorithms On A Multi-mentioning
confidence: 99%
“…The researches proposed in (Lin and Gerla, 1997;Santos et al, 2004;Luo et al, 2010;Rawashdeh and Mahmud, 2012) introduced a new category of VANET routing protocols called Cluster Based Routing (CBR). These protocols are based on dividing the nodes in the network into groups called clusters.…”
Section: Cluster Based Routing Protocolsmentioning
confidence: 99%